2013
DOI: 10.1186/2162-3619-2-19
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological analysis of primary adrenal diffuse large B-cell lymphoma: effectiveness of rituximab-containing chemotherapy including central nervous system prophylaxis

Abstract: BackgroundPrimary adrenal lymphoma (PAL) is an extremely rare subtype of extranodal non-Hodgkin’s lymphoma. Some researchers have reported some of the characteristics of PAL and its association with poor prognosis; however, the clinicopathological features of PAL remain to be elucidated.MethodsFrom 2008 to 2011 we experienced seven cases of PAL in our institutions. We retrospectively analyzed the clinical and pathological features of these patients.ResultsThe patients ranged in age from 50 to 85 years, with a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
32
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(36 citation statements)
references
References 30 publications
4
32
0
Order By: Relevance
“…A study conducted chemotherapy including the Rituximab and a central nervous system preventive therapy for diffuse large B cell lymphoma reported that the two-year survival rate was 57%, and the average survival time was 24.8 months (12). Additionally, in another multi-center study it was reported that when Rituximab-CHOP regimen was used, the two-year survival rate was 68.3%, and the disease free survival increased to 51.1% in patients diagnosed with diffuse large B cell lymphoma among primary adrenal lymphomas (13).…”
Section: Discussionmentioning
confidence: 99%
“…A study conducted chemotherapy including the Rituximab and a central nervous system preventive therapy for diffuse large B cell lymphoma reported that the two-year survival rate was 57%, and the average survival time was 24.8 months (12). Additionally, in another multi-center study it was reported that when Rituximab-CHOP regimen was used, the two-year survival rate was 68.3%, and the disease free survival increased to 51.1% in patients diagnosed with diffuse large B cell lymphoma among primary adrenal lymphomas (13).…”
Section: Discussionmentioning
confidence: 99%
“…The proposed underlying pathogenic mechanisms include immune system dysfunction, the proliferation of haematopoietic tissue in both adrenal glands after resting owing to the effects of the Epstein-Barr and JC polyoma viruses, and mutations in the p53 and c-KIT genes 11. PAL most commonly involves DLBCL (85% of cases), followed by mixed large-cell and small-cell lymphoma, T-cell lymphoma and undifferentiated lymphoma 2 12…”
Section: Discussionmentioning
confidence: 99%
“…Ana Mozos et al summarized 10 cases of PA-DLBCL patients, which 5 are affected bilaterally, during 4.5 months of random visitations, 7 cases died of lymphoma, 1 died of unrelated disease, 1 survived with the disease, 1 cured and survived [14]. Satoshi Ichikawa et al analyzed 7 cases of PA-DLBCL patients, 5 affected bilaterally, underwent R-CHOP chemotherapy, 2 year survival rate was 57% [15]. Yu Ri Kim et al analyzed 31 cases of PA-DLBCL, considered R-CHOP is an effective first line treatment, and they thought age, size of tumor, damage of adrenal gland function are relates to prognosis [16].…”
Section: Treatmentmentioning
confidence: 99%